Pengaruh Kepribadian Konsumen pada Pilihan Merek sebagai Konsep Diri pada Kategori Produk - Wardana, Dwiyadi Surya (Jurnal Ilmu Ekonomi ASET, 2011)
This research was conducted to see the influence of consumer personalityon brand selection as a self-concept on automobile product category. Avanza, Xenia,Jazz, Innova and Rush are the brand of cars that becomes an object of research. In thisresearch consumer personality consists of four variables and brand personality as selfconceptconsists of two variables. Data was collected by using survey method, and thevalidity test for items of questionnnaire using factor analysis. Then to see the influenceof consumer personality on brand selection as a self-concept on automobile productcategory this study used multiple regression analysis. Anova analysis was used to testevery car owner in the notice of a difference in consumer personality and brandpersonality as a self-concept. The empirical results, in this study a statistical test showedthat consumers used their personality to select the brand identity that match with theconcept itself.Keywords: consumer personality, brand personality, self-concept, automobile product